2011
DOI: 10.2147/ijicmr.s14331
|View full text |Cite
|
Sign up to set email alerts
|

Bothrops erythromelas snake venom induces a proinflammatory response in mice splenocytes

Abstract: Snake venom is a complex biological mixture used for immobilization and killing of prey for alimentation. Many effects are inflicted by this venom, such as coagulation, necrosis, bleeding, inflammation, and shock. This study aimed to evaluate the inflammatory activity promoted by Bothrops erythromelas and Crotalus durissus cascavella snake venom. It was observed that both B. erythromelas and C. d. cascavella venom induced higher interferon-gamma and interleukin-6 production. Nitric oxide (NO) was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
6
0
4
Order By: Relevance
“…Sua liberação já foi observada em alguns trabalhos e em pacientes que sofreram intoxicação por veneno das serpentes Bothrops (Rangel-Santos et al, 2004), no entanto, neste estudo, não houve alterações significantes na produção de IL-10 quantificadas no soro e no homogenato. A produção de IL-10 é estimulada pelas citocinas pró-inflamatórias (IL-1 e IFN), e a sua ausência pode ser devido ao tempo insuficiente para o estímulo da sua produção local (Rangel-Santos et al, 2004;Motta et al, 2009;Luna et al, 2011b).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Sua liberação já foi observada em alguns trabalhos e em pacientes que sofreram intoxicação por veneno das serpentes Bothrops (Rangel-Santos et al, 2004), no entanto, neste estudo, não houve alterações significantes na produção de IL-10 quantificadas no soro e no homogenato. A produção de IL-10 é estimulada pelas citocinas pró-inflamatórias (IL-1 e IFN), e a sua ausência pode ser devido ao tempo insuficiente para o estímulo da sua produção local (Rangel-Santos et al, 2004;Motta et al, 2009;Luna et al, 2011b).…”
Section: Resultsunclassified
“…O aumento da IL-6 no soro (Tab.1) após seis horas da inoculação está em conformidade com a literatura, que evidencia relatos desse aumento em pacientes ou animais de experimentação intoxicados com veneno botrópico (Lomente et al, 1993;Ávila-Aguero et al, 2001;Laing et al, 2003;Escocard et al, 2006;Luna et al, 2011a;Luna et al, 2011b). As citocinas quando quantificadas no homogenato, também houve um aumento da IL-6 após seis horas (Tab.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A study performed by Luna et al (39) showed that, Bothrops erythromelas and Crotalus durissus cascavella venoms induced high interferon-gamma and IL-6 production in mouse splenocytes. Nitric oxide was signifi cantly produced in the splenocytes only by B. erythromelas venom, which also induced a higher rate of cell death than C. durissus cascavella venom did.…”
Section: Overview On Bothrops Erythromelas Venommentioning
confidence: 99%